2010
DOI: 10.1177/0886260510383039
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Stereotypical Beliefs, Participant Gender, and Survivor Weight on Sexual Assault Response

Abstract: The present study explored the influence of survivor weight and participant gender, rape myth acceptance, and antifat attitudes on perceptions of sexual assault. Using an online survey tool, a community sample of 413 adult Canadian residents reviewed a hypothetical sexual assault scenario and completed a series of evaluations and attitudinal questionnaires. Generalized linear model analyses revealed that participants were more likely to hold the survivor responsible, excuse the perpetrator's actions, and respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
36
2
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(48 citation statements)
references
References 34 publications
8
36
2
2
Order By: Relevance
“…Other studies, however, have found otherwise (Clarke & Stermac, 2011;Krulevitz & Nash, 1979). Specifically, Clarke and Stermac (2011) found that women exposed to vignettes about physically attractive rape survivors (thin versus overweight) tended to blame her and hold her more accountable. Similarly, Krulevitz and Nash (1979) found that women were overall more stigmatizing of rape victims than men and attributed more fault to the victim when the attempted rape was completed than when it was not.…”
Section: Gender Differences In Reactions To Rape Disclosuresmentioning
confidence: 96%
“…Other studies, however, have found otherwise (Clarke & Stermac, 2011;Krulevitz & Nash, 1979). Specifically, Clarke and Stermac (2011) found that women exposed to vignettes about physically attractive rape survivors (thin versus overweight) tended to blame her and hold her more accountable. Similarly, Krulevitz and Nash (1979) found that women were overall more stigmatizing of rape victims than men and attributed more fault to the victim when the attempted rape was completed than when it was not.…”
Section: Gender Differences In Reactions To Rape Disclosuresmentioning
confidence: 96%
“…However, over half of the studies found in this area failed to support our expectation of a focus on positive outcomes for women who have been raped in the rape survivor literature; rather, four studies focused on individuals' mythic beliefs, blaming attitudes, and rape minimizing perceptions as they emerged in a variety of situations. These negative beliefs, attitudes, and perceptions were shown to emerge in naturalistic conversations about rape (Anderson, 1999), in relation to other prejudices related to the target, such as anti-fat attitudes (Clarke & Stermac, 2011) and racial stereotypes (Donovan, 2007), and even when individuals were instructed to contemplate rape scenarios in which the women who had been raped were close friends or relatives (Ellis, O'Sullivan, & Sowards, 1992). Although these outcomes were not expected, they indicated a paucity in the literature to be addressed in future research by examining variation in positive rape-related beliefs, attitudes, perceptions, and behaviors that individuals may have, but which may not be spontaneously reported in qualitative assessments or accessible via traditional quantitative measures (e.g., assessing blame attributions, acceptance of rape myths).…”
Section: Rape-related Beliefs Attitudes Perceptions and Behaviors mentioning
confidence: 96%
“…Each of these factors has been found to correlate positively with victim responsibility ratings (for reviews, see Sleath & Bull, 2017 ; Van der Bruggen & Grubb, 2014 ; Whatley, 1996 ). Finally, physical attractiveness of the victim appears to be positively associated with both victim credibility and victim responsibility (for examples of studies about the association between physical attractiveness and credibility ratings, see Clarke & Stermac, 2011 ; Vrij & Firmin, 2001 ; Yamawaki, Riley, Rasmussen, & Cook, 2015 ; for a review of studies about the association between psychical attractiveness and responsibility ratings, see Whatley, 1996 ). For all these factors it seems worthwhile to investigate whether they relate to decision makers’ feelings of sympathy for the victim and, if so, whether these feelings explain their associations with victim credibility and responsibility.…”
Section: Discussionmentioning
confidence: 99%